Kualitas Pelayanan Pada MA Al-Badriyah Di Kabupaten Sukabumi - Sagita, Novi Evalin; Ningsih, Ratih Hendra (ECONEUR (Journal of Economics and Entrepreneurship), 2024)
One of the things that influences the success of students in the learning process at school is the quality of services provided by the school to students. Good service quality will improve the school's image and reputation in the eyes of the community. The aim of this research is to determine the quality of service at MA Al-Badriyah in Sukabumi Regency. The method used by researchers is a descriptive quantitative method. Data collection through interviews, observations and questionnaires. The level of community satisfaction is measured using 6 dimensions, namely service facilities, reliability, responsiveness, guarantee, price and empathy. Results from several indicators taking as many as 104 respondents. Obstacles that occur in the service process at MA Al-Badriyah include: toilet facilities that are not comfortable, many toilets that need to be repaired, inadequate library space, narrow rooms, few book facilities, and the environment is not clean, some teachers are less than optimal in the process teaching, teachers and staff are less responsive in providing services to students, the information conveyed to students still contains inaccuracies, the school is less open regarding financial matters, and the school does not respond to any complaints/complaints from students. The conclusion of this research shows that the research results contribute to the quality of service at MA Al-Badriyah in Sukabumi Regency and student satisfaction can be used as input or consideration in developing services in the future.